Harmonizing the Qur’ān and Modern Science: A Critical Study in the Context of the Indian Subcontinent - Razzaq, Zain; Nawaz, Rab (Journal of Islamic Thought and Civilization, 2025)
This study aims to examine the various approaches taken by Muslim scholars of the Indian Subcontinent in response to modern science, particularly during the 19th and 20th centuries, when colonial epistemology profoundly influenced Muslim thought in the region. These approaches seek to address a common problem: resolving the perceived incompatibility between Islam and modern science. However, they offer distinct solutions in this regard. The first section provides a comprehensive overview of the methods adopted by proponents of these approaches, highlighting the strategies used to harmonize the Qur’ān with modern science, the epistemological problems they identify and the theological solutions they offer. The second part presents a critical analysis of the attempts to harmonize the Qur’ān and modern science from the perspective of those who completely reject both the modern and Islamic versions of science. This paper adopts a qualitative approach, employing historical and analytical research methods to trace the development of these debates. Primary sources have been given priority to capture the authentic voices of the scholars involved, while secondary sources, including contemporary academic research, have also been used where necessary to provide contextual and comparative analysis. The paper aims to contribute to a deeper understanding of the modern intellectual history of the Muslim world in response to modern science and to highlight the ongoing relevance of these debates in contemporary Islamic thought.